EFFECTS OF SINGLE-VISIT SUBGINGIVAL ULTRASONIC DEBRIDEMENT WITH ADJUNCTIVE MINOCYCLINE GEL ON PERIODONTAL AND INFLAMMATORY PARAMETERS IN PATIENTS WITH TYPE 2 DIABETES - Jundaeng, Jarupat; Nantakeeratipat, Teerachate; Thongsiri, Chuencheewit; Laosrisin, Narongsak (Srinakharinwirot University Journal of Sciences and Technology, 2022)
Objective:To evaluated the clinical periodontal and inflammatory outcomes of adjunctive minocycline in patients with both periodontitis and type 2 diabetes mellitus (T2DM). Methods: Sixty patients with T2DM diagnosed with periodontitis were recruited and divided into control and test groups. All participants underwent a single-visit subgingival ultrasonic debridement, but only the test group received adjunctive sustained-release minocycline gel immediately afterward. Periodontal parameters, cytokines (IL-1b, IL-6, TNF-α and MCP-1), adiponectin, and Porphyromonas gingivalis (Pg) antibody were measured at baseline, 3 and 6 months after treatment. Results: Patients in both groups showed significant improvement in all clinical parameters after three and six months. The mean probing depth reduction and clinical attachment level gain after three months were significantly improved in the test group compared to the control group (p<0.05). IL-6, TNF-α, and MCP-1 were significantly reduced at the 3-month visit in both groups. Adiponectin was significantly increased at 6 months only in the test group. Moreover, Pg antibody was significantly reduced in both groups. Conclusion: Subgingival ultrasonic debridement combined with locally administered minocycline gel was effective in improving periodontal and inflammatory parameters in patients with T2DM at 3 months after treatment.